Mathematical proficiency among female teachers of the first three grades in Jordan and its relationship to their mathematical thinking - Alfayez, Mona Qutaifan Ershed (Frontiers in Education, 2022)
Aim: The present study aimed at investigating the association of the mathematical proficiency and mathematical thinking skills among female teachers of the first three grades in public schools of Amman city, Jordan. Method: The study adopted the descriptive analytical research approach. A sample of 174 female teachers of the first three grades was recruited in the present study. To collect data, the study used a mathematical proficiency tests (39 items) covering the domains of the conceptual understanding, procedural fluency, strategic competency, adaptive reasoning, and the productive desire. In addition, the study used a mathematical thinking skills test consisted of (20) items distributed over seven mathematical thinking skills; they were: Induction skill, conclusion skill, symbolizing skill, logical thinking skill, guessing skill, demonstration skill, and modeling skill. Data were analyzed using SPSS software (v. 26). Results: The study findings showed that female teachers of the first three grades had a moderate level of mathematical proficiency (43.60±16.04), a good level of mathematical thinking skills (6.51±4.628). In addition, the study found significant statistical positive correlation between mathematical proficiency and mathematical thinking skills (r=0.681, p≤0.05) among female teachers of the first three grades in Amman. Conclusion: The study concluded that mathematical proficiency is significantly associated with mathematical thinking skills in their domains. The study recommended increasing female teachers’ competencies and skills related to mathematical proficiency and mathematical thinking throughout intensive courses and workshops.